ANALISIS PERBANDINGAN PARTISIPASI MASYARAKAT KAWASAN PERUMAHAN DENGAN KAWASAN PERKAMPUNGAN DALAM PERENCANAAN PEMBANGUNAN - Winfrit Kasse; Willy Tri Hardianto; Dewi Citra Larasati (Universitas Tribhuwana Tunggadewi, 2017)
Abstract : Participatory development planning is an important issue of development that become demand of the people. This is related to the result of the evaluation that the approach of the development that is top-down rated less answer the basic issues and the needs of the community. The type of research is qualitative research with data collection technique by interview, observation and documentation, while the informants in this study is the Village Authorities and the Communities with Snowball sampling. The public participation of the housing area with the township area in the perspective of development in the Village of Landungsari, Sub-district of Dau, Malang Regency as follows: Planning of development through Musrenbangdes participation or level of community participation residential/housing area in development planning is still low, this is happening because in general people of the housing area have activities or work either as an entrepreneur, lecturer, teacher as well as Government Employee. While the level of participation of the people live in the township area in development planning through Musrenbangdes is larger both involved as an object or as a subject. Factors that affect the role of community participation in the housing area and the township/village area in the development planning in the Village of Landungsari: education, awareness, level of income. Keywords: Participation, People/Community, Development Abstrak : Perencanaan pembangunan partisipatif merupakan isu penting pembangunan yang menjadi tuntutan masyarakat. Hal ini terkait dengan hasil evaluasi bahwa pendekatan pembangunan yang bersifat top-down dinilai kurang menjawab persoalan dasar dan kebutuhan masyarakat. Jenis penelitian yang digunakan yaitu jenis penelitian kualitatif dengan teknik pengumpulan data melalui wawancara, observasi dan dokumentasi, sedangkan informan dalam penelitian ini adalah Pemerintah Desa dan Masyarakat dengan penarikan sampel secara snowbal sampling. Peran serta masyarakat kawasan perumahan dengan perkampungan dalam perspektif pembangunan di Desa Landungsari Kecamatan Dau Kabupaten Malang sebagai berikut: Perencanaan pembangunan melalui Musrenbangdes peran serta atau tingkat partisipasi masyarakat kawasan perumahan dalam perencanaan pembangunan masih rendah, hal ini terjadi dikarenakan pada umumnya masyarakat perumahan mempunyai pekerjaan sebagai pengusaha, dosen, guru, wiraswasta serta Pegawai Negeri Sipil. Sedangkan tingkat partisipasi masyarakat yang tinggal di perkampungan dalam perencanaan pembangunan melalui Musrenbangdes lebih besar baik terlibat sebagai obyek maupun sebagai subyek. Faktor-faktor yang mempengaruhi peran partisipasi masyarakat kawasan perumahan dengan perkampungan dalam perencanaan pembangunan di Desa Landungsari: pendidikan, kesadaran, tingkat pendapatan. Kata kunci: Partisipasi, Pembangunan